1977
DOI: 10.1136/bmj.1.6061.607
|View full text |Cite
|
Sign up to set email alerts
|

Metronidazole in prevention and treatment of bacteroides infections in elective colonic surgery.

Abstract: Most workers agree that the cell that gives rise to colonies in the agar colony system is equivalent to the granulopoietic stem cell. 8 The formation of colonies, however, requires the activatton of this cell and the serial proliferation of its progeny, and we cannot distinguish from our data whether quinine had a toxic effect on either or both of these mechanisms.Our results encourage the further use of the marrow culture system for trying to identify in vitro drugs responsible tor agranulocytosis in particul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
21
0
4

Year Published

1978
1978
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 128 publications
(27 citation statements)
references
References 12 publications
(1 reference statement)
2
21
0
4
Order By: Relevance
“…The above results compare favourably with those of Willis et al [13][14][15] using me tronidazole. The ease of administration, and one-dose therapeutic regimen of tinidazole, make it a promising new drug in the pro phylaxis and possibly treatment of anaer obic infections.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…The above results compare favourably with those of Willis et al [13][14][15] using me tronidazole. The ease of administration, and one-dose therapeutic regimen of tinidazole, make it a promising new drug in the pro phylaxis and possibly treatment of anaer obic infections.…”
Section: Discussionsupporting
confidence: 81%
“…Post-operative wound/vault infections in control patients cleared spon taneously (18 cases) or responded to imidazole therapy, with or without ampicillin and kanamycin (7 cases). These data suggest that tinidazole may be a useful adjunct in imida zole prophylaxis and treatment of anaerobic infection.Anaerobes have been strongly implicated in the pathogenesis of post-operative ab dominal infections [1,5,10]; it has been shown that the prophylactic administration of metronidazole decreases the incidence of such infections, especially after colorectal or gynaecological surgery [13][14][15].Tinidazole, another member of the imi dazole group [4,9,11,16,17], has been shown to inhibit anaerobes in vitro, with minimum inhibitory concentrations margin ally lower than those seen with metronida zole for the same organisms [9,16], This re port describes the effect of prophylactic tini dazole therapy on the anaerobe vaginal car riage rate and development of post-operawith tinidazole prophylaxis, 50 controls) untive anaerobic infection in 100 patients (50 …”
mentioning
confidence: 99%
“…Many of the organisms in these mixtures were potential patbogens, but there is some evidence that the anaerobes are the more significant pathogens. Willis et al (1975Willis et al ( , 1976Willis et al ( , 1977 showed that treatment of the anaerobic component of infections related to the appendix, colon, rectum and female genital tract with metronidazole controlled the infections, and Jones, Willis & Ferguson (1978) obtained healing of infected decubitus ulcers with topical metronidazole. However, the facultative and aerobic species in the mixtures should not be ignored; there may be synergy between components of the mixed flora (Tally & Gorbach, 1979) …”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have shown that preoperative antibiotic prophylaxis reduces cases of septic complications after surgery of gastrointestinal tract. 7,8 In surgical patients, antimicrobial prophylaxis is indicated particularly in the surgery of large intestine and rectum, where anaerobic bacteria, such as Bacteroides fragilis, predominate. 9 Currently, there are many combinations of antibiotics and chemotherapeutic agents used in surgical prophylaxis.…”
Section: Introductionmentioning
confidence: 99%